Polyclonal antibody–based immunohistochemical detection of intraleukocytic Theileria parasites in roan and sable antelopes. (November 2021) - Clift, Sarah J.; Martí-Garcia, Bernat; Phaswane, Rephima M.; Mitchell, Emily P.; Josemans, Antoinette I.; Vorster, Ilse; Koeppel, Katja N.; Fehrsen, Jeanni
Theileria parasites commonly infect African wild artiodactyls. In rare roan ( Hippotragus equinus ) and sable ( H. niger ) antelopes, Theileria sp. (sable)-associated calf mortalities constrain breeding programs. The pathogenicity of most leukocyte-transforming Theileria spp. originates in their invasion of and multiplication in various mononuclear leukocytes, the transformation of both infected and uninfected leukocytes, and their infiltration of multiple organs. Understanding the pathogenesis of theileriosis can be improved by the use of immunohistochemistry (IHC) to identify the localization of the parasites in tissue sections. Our aim was to develop a reproducible IHC assay to detect leukocyte-associated Theileria parasites in formalin-fixed, paraffin-embedded roan and sable tissues. Polyclonal antibodies were purified from the sera of 5 roans from an area endemic for Theileria sp. (sable) and tested for IHC reactivity in 55 infected and 39 control roan and sable antelopes, and for antigen and species cross-reactivity in an additional 58 cases. The 3 strongest antibodies consistently detected intraleukocytic theilerial antigens in known positive cases in roan and sable antelopes, and also detected other Theileria spp. in non-hippotraginid wild artiodactyl tissues. The antibodies did not cross-react with other apicomplexan protozoa, with the exception of Cryptosporidium . Given that PCR on its own cannot determine the significance of theilerial infection in wild ruminants, IHC is a useful laboratory test with which to confirm the diagnosis in these species.